Annual Dynamics of Retrogressive thaw slumps across NE Siberia with LandTrendr - Runge, Alexandra; Nitze, Ingmar; Grosse, Guido (American Geophyscal Union, 2021)
Permafrost temperatures increase globally and lead to extensive permafrost thaw. With increasing air temperatures, changing precipitation regimes, increased intensity and frequency of extreme events, and disturbances such as wildfires, permafrost is increasingly vulnerable to thawing. Permafrost thaw either occurs gradually over decades or is initiated through rapid and abrupt permafrost disturbance processes, which can develop within a few days to years. The impact of such rapid disturbances on Arctic-Boreal ecosystems can be drastic on local to regional-scale and a global impact has been suggested through soil carbon mobilisation. Retrogressive thaw slumps (RTS) are highly dynamic and abrupt permafrost disturbance features that result from slope failure from thawing of ice-rich permafrost. Although RTS are small-scale features, they often occur in clusters, significantly impacting the surrounding landscapes and ecosystems at high temporal scales. The occurrence and thawing activity of RTS signifies an increased permafrost vulnerability. So far, previous assessments focused on mapping RTS with remote sensing imagery at local-scale and deriving temporal information from few snapshots in time. A continuous and high temporal assessment of the disturbance dynamics at a representative larger-scale is still missing. Thus, our main objective was to map and monitor RTS on a continental-scale and assess their annual temporal thaw dynamics in Northeast Siberia. We adapted and parametrised LandTrendr, an automated temporal segmentation algorithm, to identify the abrupt annual RTS disturbances in Landsat and Sentinel-2 time series data. Additionally, we applied spectral and spatial masks and a machine learning classification for improved RTS mapping. Our results show the first continental-scale mapped RTS distribution in NE Siberia and their annual thaw dynamics from. Overall, the RTS thaw dynamics steadily increased in NE Siberia during the assessment period. At the same time, local assessments revealed distinct periods ...